2008
DOI: 10.3201/eid1402.070981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Feline Leukemia Virus from Florida Panthers

Abstract: The emergent strain of FeLV, a novel subgroup A, was probably transmitted to panthers by a domestic cat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 29 publications
2
81
0
Order By: Relevance
“…The relationship between predator-prey interactions and viral transmission is not well studied and may represent a process by which predators accumulate pathogens by a mechanism that is similar to the process of bioaccumulation of environmental toxins (61). For example, feline leukemia virus has spilled over from domestic cats and caused outbreaks with high morbidity in Florida panthers on multiple occasions (62,63). Another example is the recent discovery of a novel feline gammaherpesvirus that appears to be transmitted from bobcats to mountain lions (64).…”
Section: Figmentioning
confidence: 99%
“…The relationship between predator-prey interactions and viral transmission is not well studied and may represent a process by which predators accumulate pathogens by a mechanism that is similar to the process of bioaccumulation of environmental toxins (61). For example, feline leukemia virus has spilled over from domestic cats and caused outbreaks with high morbidity in Florida panthers on multiple occasions (62,63). Another example is the recent discovery of a novel feline gammaherpesvirus that appears to be transmitted from bobcats to mountain lions (64).…”
Section: Figmentioning
confidence: 99%
“…4,13 In addition, serosurveys of neotropical felids indicate antibodies to FeLV in all neotropical species maintained in captivity, except Panthera onca, and antibodies to FeLV in two free-ranging Panthera concolor. 4 Since serious clinical disease leading to death has been described in some wild felids, 1 FeLV infection is recognized as an emerging disease that may contribute to declines in these populations.…”
Section: Brief Communicationmentioning
confidence: 99%
“…The virus isolate, designated FeLV-Pco, was shown to be closely related and perhaps identical to FeLV-945. Indeed, it was suggested that the outbreak may have been caused by cross-species transmission from a domestic cat, perhaps one infected with FeLV-945 (Brown et al, 2008). If recombination with endogenous FeLV-related elements is not required for disease induction by FeLV-945, then wild felids lacking such sequences in the genome may indeed be susceptible to infection and disease by this virus.…”
Section: Resultsmentioning
confidence: 99%